# g o f =? f(x)=(x-1)^2 and g(x)=x^1/2

ncchemist | eNotes Employee

Posted on

Finding g(f(x)) is the same as subtituting the f(x) function into the variable for g(x) and simplifying.  In this case it involves taking the square root of the squared term, thereby cancelling the exponents:

g(f(x)) = [(x-1)^2]^1/2 = (x-1)^1 = x-1

g o f = x-1

Educator Approved

tonys538 | Student, Undergraduate | (Level 1) Valedictorian

Posted on

The  function` f(x)=(x-1)^2` and `g(x)=x^1/2`

`gof(x) = g(f(x))`

= `g((x - 1)^2)`

= `((x - 1)^2)^(1/2)`

= `(x - 1)^(2*1/2)`

= x - 1

The complex function `gof(x) = x - 1`

giorgiana1976 | College Teacher | (Level 3) Valedictorian

Posted on

We'll write the composition of the functions g and f as it follows:

gof(x) = g(f(x))

f(x) = (x-1)^2 and g(x) = sqrt x

We'll replace x by f(x), in the expresison of g(x).

g(f(x)) = g((x-1)^2)

g((x-1)^2) = sqrt [(x-1)^2]

g((x-1)^2) = |x-1|

The result of composition of the functions is:

(gof)(x) = g(f(x)) = |x-1|